Depression and obesity: can the cycle be broken?. (1st March 2018) - Romain, Karen; Webb, Timothy; Kumar, Manoj
SUMMARY: Obesity and depression are conditions that have been linked through a great number of interesting mechanisms. To fully understand the implications of treatment choices it is necessary to continue to investigate the physiology of these two conditions. By examining the background of these problems and considering factors such as stress response, neurological change and systemic inflammation, we propose a cycle linking depression and obesity. With reference to this cycle, we discuss management options, focusing particularly on prescribing choices and current guidelines. An assessment of the medication options is provided demonstrating that prescribing choices can have a significant impact on ongoing physical health. The aim of this discussion is to raise awareness of current research and progress and to see whether the cycle of depression and obesity can be broken. LEARNING OBJECTIVES: Update knowledge of the mechanisms linking depression and obesity Understand the impact of medication on the cycle linking the two Consider how we can improve outcomes for patients with depression and/or obesity DECLARATION OF INTEREST: None.